2018
DOI: 10.2494/photopolymer.31.81
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Phase Transition of Hybrid Films of Azobenzene-based Photochromic Amorphous Molecular Materials and Poly(vinyl acetate)

Abstract: Homogeneous hybrid films of azobenzene-based photochromic amorphous molecular materials, 4-[bis(4-methylphenyl)amino]azobenzene (BMAB) and 4-[phenyl(biphenyl-4yl)amino]azobenzene (PBAB), together with poly(vinyl acetate) (PVAc) were obtained by spin-coating method. Both BMAB-PVAc and PBAB-PVAc films exhibited reversible phase separation-resolution phenomena by thermal treatments. When the resulting phaseseparated films were irradiated with 488 nm-laser beam at appropriate temperature, phase transition was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nakano H produces photochromic molecular materials by spin coating. He found that the photochromic amorphous molecular material film based on azobenzene showed reversible phase separation resolution through heat treatment [4]. Sergey studied the preparation of highpurity composites and nano materials with photoactive compounds, and summarized the physical properties of organic photochromic ions [5], indicating that nano organic photochromic new materials are also in the research scope of researchers.…”
Section: Related Workmentioning
confidence: 99%
“…Nakano H produces photochromic molecular materials by spin coating. He found that the photochromic amorphous molecular material film based on azobenzene showed reversible phase separation resolution through heat treatment [4]. Sergey studied the preparation of highpurity composites and nano materials with photoactive compounds, and summarized the physical properties of organic photochromic ions [5], indicating that nano organic photochromic new materials are also in the research scope of researchers.…”
Section: Related Workmentioning
confidence: 99%
“…For example, we have reported that spincoated films of diarylaminobenzaldehyde-based emitting amorphous molecular materials exhibited vapochromic emission [11]. In addition to such materials with single component systems, we have recently been studying the creation of hybrid systems of amorphous molecular materials with other materials exhibiting smart functions [13][14][15][16][17][18][19][20][21][22][23]. We have reported that the hybrid films of aminoazobenzene-based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture [20].…”
Section: Introductionmentioning
confidence: 99%
“…Rearrangement of polymer chains to be adapted to the structural deformation of TCNQ is suppressed in the rigid glass state in comparison to the rubber state. [25,26] Therefore, the fluorescence intensity is expected to show variation, when the temperature is changed across Tg. We use three different polymers, poly(methyl acrylate) (PMA), poly(vinyl acetate) (PVAc), and poly(methyl methacrylate) (PMMA) (Fig.…”
mentioning
confidence: 99%